Mu and kappa opioid modulation of the hypothalamic serotonergic neurotransmission in the ovariectomized and steroid-primed rat - Yilmaz, B; Gilmore, DP (Lippincott Williams & Wilkins, 1999)
We have investigated the effects of mu- and kappa-opioid agonists on hypothalamic indolamine concentrations and luteinizing hormone (LH) release in the ovariectomized and steroid-primed rat. The opioid agents and sterile saline were intracerebroventricularly infused under ketamine anaesthesia and blood samples collected at hourly intervals on the afternoon of the anticipated LH surge. At the end, the rats were decapitated and the medial preoptic area (MPOA), suprachiasmatic nucleus (SCN), median eminence (ME) and arcuate nucleus (ARN) surgically isolated by micropunch. The indolamine content in these samples was determined by high performance liquid chromatography with an electrochemical detector. Plasma LH levels were measured by radioimmunoassay. Both diamorphine (mu-agonist) and U-69593 (K-agonist) significantly reduced 5-HT concentrations in all the hypothalamic regions examined. 5-HIAA levels were decreased by the kappa-agonist in the MPOA, SCN and ME and by the mu-agonist in only the MPOA. Plasma LH levels were either low or undetectable in all groups. These results suggest that activation of mu- and kappa-opioid receptors inhibits the hypothalamic serotonergic neurotransmission around the time of the LH surge. It is thought that the ketamine anaesthesia interfered with LH secretory systems. Med Sci Res 27:91-94 (C) 1999 Lippincott Williams & Wilkins.
Keywords: 5-hydroxyindoleacetic acid; 5-hydroxytryptamine; HPLC; ketamine; luteinizing hormone; opioids